2015
DOI: 10.1007/s10661-015-4532-4
|View full text |Cite
|
Sign up to set email alerts
|

Thiamethoxam degradation by Pseudomonas and Bacillus strains isolated from agricultural soils

Abstract: Twelve bacterial species were evaluated to know the degradation pattern of thiamethoxam in liquid medium. All the bacterial species could actively degrade phorate in a mineral salt medium containing phorate (50 μg ml(-1)) as sole carbon source. As these species have ability to degrade, we used these for the degradation of thiamethoxam--a neonicoitinoids. Screening of 12 active phorate-metabolizing bacterial species resulted in selection of Bacillus aeromonas strain IMBL 4.1 and Pseudomonas putida strain IMBL 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Although toxic compounds present in natural waters are removed mainly by photodegradation and biodegradation, TMX is poorly degraded by hydrolysis . In fact, TMX biodegradation with pure Rhizobacterium , Pseudomonas and Bacillus strains proved largely inefficient (TMX conversion after 15 days was <45%) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although toxic compounds present in natural waters are removed mainly by photodegradation and biodegradation, TMX is poorly degraded by hydrolysis . In fact, TMX biodegradation with pure Rhizobacterium , Pseudomonas and Bacillus strains proved largely inefficient (TMX conversion after 15 days was <45%) …”
Section: Introductionmentioning
confidence: 99%
“…11 In fact, TMX biodegradation with pure Rhizobacterium, Pseudomonas and Bacillus strains proved largely inefficient (TMX conversion after 15 days was <45%). 12,13 Advanced oxidation processes (AOPs), which provide highly competitive water treatments for removing pesticides refractory to conventional methods, appear to be a good choice for TMX removal. In recent years, a variety of AOPs, but particularly photocatalysis with titanium dioxide (TiO 2 ) and photo-Fenton treatments, have been used successfully to degrade neonicotinoids.…”
Section: Introductionmentioning
confidence: 99%
“…The same study found no difference in the dissipation of clothianidin from autoclaved soils or nonsterile aerobic soils, demonstrating that microbes are not a factor involved in the degradation of this neonicotinoid. This behavior is in contrast with that of thiamethoxam, which can be degraded by Bacillus aerophilus and Pseudomonas putida in soils (Rana et al 2015). Laboratory cultures (37°C) of these soil microbes were capable of degrading 50 mg/kg thiamethoxam in soil by 38% (P. putida) and 45% (B. aerophilus), with no production of metabolites.…”
Section: Soilmentioning
confidence: 82%
“…A strain of Pseudomonas aeruginosa isolated from rice-cultivated soil has the capacity to degrade propiconazole [54]. Other strains of the genus Pseudomonas isolated from agricultural soil degrade thiamethoxam [55].…”
Section: Resultsmentioning
confidence: 99%